STRATEGI PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI KABUPATEN SUMBAWA - Pamungkas, Binar Dwiyanto; Stiawati, Hasta Rani (Pusat Riset dan Publikasi, 2025)
The purpose of this study was to know the development strategy of micro, small and medium enterprises in Sumbawa District. The type of this study was descriptive study. The sources of data in this study were primary and secondary data. The tools used to collect data were observation, questionnaires and documentation. The population and sample were divided into three parts with the criteria of bureaucrat respondents, academic respondents and respondents of MSME actors whom were still active. The number of samples in this study was 30 expert respondents from bureaucrats, academics and MSME actors who were still active. The technique of data analysis was Analytic Hierarchy Process (AHP). The results of the study showed that the priority strategies for developing micro, small and medium enterprises in Sumbawa District namely: 1) Innovation with product development, 2) Selection of strategic sales locations/places, 3) Human resource knowledge in this case reducing risk and using technology, 4) Good coordination and cooperation among MSMEs, 5) Government training programs to improve the competence and brand product of MSME had priority vector. Innovation with product development was in the first position in this study was means that the main aspect or important in the development of micro, small and medium enterprises in Sumbawa District. By having innovative products, MSMEs can differentiate themselves from competitors, introduce products so that can attract new customers and increase competitiveness.